Immobilized enzymes as potent antibiofilm agent. (24th June 2022) - Lahiri, Dibyajit; Nag, Moupriya; Dey, Ankita; Sarkar, Tanmay; Ray, Rina Rani; Rebezov, Maksim; Shariati, Mohammad Ali; Thiruvengadam, Muthu; Simal‐Gandara, Jesus
Abstract: Biofilm has been a point of concern in hospitals and various industries. They not only cause various chronic infections but are also responsible for the degradation of various medical appliances. Since the last decade, various alternate strategies are being adopted to combat the biofilm formed on various biotic and abiotic surfaces. The use of enzymes as a potent anti‐fouling agent is proved to be of utmost importance as the enzymes can inhibit biofilm formation in an eco‐friendly and cost‐effective way. The physical and chemical immobilization of the enzyme not only leads to the improvement of thermostability and reusability of the enzyme, but also gains better efficiency of biofilm removal. Immobilization of amylase, cellobiohydrolase, pectinase, subtilisin A and β‐N‐acetyl‐glucosaminidase (DspB) are proved to be most effective in inhibition of biofilm formation and removal of matured biofilm than their free forms. Hence, these immobilized enzymes provide greater eradication of biofilm formed on various surfaces and are coming up to be the potent antibiofilm agent.